Pengaruh Manajemen Laba Riil dan Kinerja Keuangan terhadap Agresivitas Pajak dengan Pemoderasi Dewan Komisaris Independen - Aries Romli; Hexana Sri Lastanti (Jurnal Syntax Admiration, 2024)
This research aims to examine the influence of real abnormal cash flow operation (CFO) earnings management, real abnormal production earnings management, real abnormal discretionary expense earnings management, profitability, leverage on tax aggressiveness with an independent board of commissioners as a moderating variable. The population of this research is non-cyclicals consumer good companies listed on the Indonesia Stock Exchange for the 2020-2021 period and the sample tested was 81 data taken based on the purposive sampling method. The data used in this research is secondary data in the form of annual reports and financial reports. This research uses multiple linear regression analysis and moderated regression analysis. The results of this research show that profitability and leverage have a positive effect on tax aggressiveness. Meanwhile, cash flow operation (CFO) abnormal real profit management, abnormal production real profit management, abnormal discretionary expense real profit management have a negative effect on tax aggressiveness. The moderating variable of the independent board of commissioners cannot moderate the influence of cash flow operation (CFO) abnormal real earnings management, abnormal production real earnings management, abnormal real earnings management discretionary expense, profitability, and leverage on tax aggresiveness.